THE APPRAISAL ANALYSIS OF CHARACTER IN RESOLUTION PART OF THE OLD MAN AND THE SEA BY ERNEST HEMINGWAY - Piscayanti, Kadek Sonia (Institut Agama Islam Negeri Ponorogo, 2020)
This research aimed to analyze the character of Santiago in resolution part of the novel “The Old Man and The Sea” by Ernest Hemingway using SFL Appraisal Theory. From the data analysis, it was found that attitude (affect) and graduation (force) dominated the appraisal items in the resolution part of “The Old Man and The Sea”. In total there were 34 appraisal items found. There were 11 appraisal items on affect found (29.72%), 3 items on judgment (8.1%), 1 item on appreciation (2.7%), 5 items on engagement (13.5%) and 17 items on graduation (45.94%). Those expressions developed from character revelation through dialogue and narration on setting, and those difference marks significant importance of character’s development in the resolution part. The character revelations found in the resolution part are: reflective, affectionate (caring and loving), humble, wise, realistic, and optimistic. This research showed the contribution of appraisal theory, especially attitude and graduation to develop a character in fiction, to be more exact, vivid, and naturally convincing. In the context of language teaching, the awareness of linguistics expression, language evaluations on meanings and values are relevant to be introduced from early to get better understanding of the language.